Bleeding after dilatation and curettage: the efficacy of transcatheter uterine artery embolisation. Issue 12 (December 2015) - Song, Y.; Shin, J.H.; Yoon, H.-K.; Kim, J.W.; Ko, G.-Y.; Won, H.-S.
Abstract : Aim: To evaluate safety and clinical outcomes of uterine artery embolisation (UAE) for bleeding after dilatation and curettage (D&C) performed for abortion or termination. Materials and methods: The outcomes were analysed in 11 patients who underwent UAE for bleeding after D&C for missed abortions ( n =8), caesarean scar pregnancies ( n =2), or planned termination ( n =1) between October 2001 and December 2013. Angiograms and medical records were retrospectively reviewed in order to obtain the patients' baseline characteristics, technical/clinical success rate, complications, and follow-up data regarding menstruation. Results: Technical success, defined as successful catheterisation of both uterine arteries with embolisation to haemostasis, was 100%, whereas clinical success, defined as cessation of bleeding after the initial session of UAE and without the need for additional UAE or surgery for the purpose of haemostasis, was 81.8% (nine of 11). In the two patients with clinical failure due to recurrent vaginal bleeding after UAE, one patient underwent repeat UAE and showed a successful outcome, whilst the other patient required hysterectomy with pathological results of placenta increta. Two other patients underwent hysterectomy for placenta percreta or hydatidiform mole-mimicking remnant placenta. None of the patients included in the present series had procedure-related complications. Menstruation resumed in all eight patients with an intact uterus during the mean follow-up period. Conclusion: UAE may be a safe and effective treatment for bleeding after D&C, especially for women who wish to preserve their fertility; however, hysterectomy may be indicated for patients with a placental abnormality. Highlights: We evaluate outcomes of uterine artery embolization for bleeding after D&C. UAE may be a safe and effective treatment for bleeding after D&C. Hysterectomy may be indicated for patients with a placental abnormality.